2023
DOI: 10.3389/fmicb.2023.1117965
|View full text |Cite
|
Sign up to set email alerts
|

Association of gut microbiota and SCFAs with finishing weight of Diannan small ear pigs

Abstract: Finishing weight is a key economic trait in the domestic pig industry. Evidence has linked the gut microbiota and SCFAs to health and production performance in pigs. Nevertheless, for Diannan small ear (DSE) pigs, a specific pig breed in China, the potential effect of gut microbiota and SCFAs on their finishing weight remains unclear. Herein, based on the data of the 16S ribosomal RNA gene and metagenomic sequencing analysis, we found that 13 OTUs could be potential biomarkers and 19 microbial species were ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 85 publications
(57 reference statements)
1
8
0
Order By: Relevance
“…Members of the class Clostridia , including Ruminococcaceae , are often involved in SCFA production in animal intestines (Barcenilla et al 2000 , Zhang et al 2018 , Lan et al 2023 ). The genome of AC_RUM01 contained genes involved in SCFA production, which could be beneficial to the host (Li et al 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Members of the class Clostridia , including Ruminococcaceae , are often involved in SCFA production in animal intestines (Barcenilla et al 2000 , Zhang et al 2018 , Lan et al 2023 ). The genome of AC_RUM01 contained genes involved in SCFA production, which could be beneficial to the host (Li et al 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that species of this genus are more likely to be proteolytically active members than species of Lactobacillus . The effect of Streptococcus on the host intestine is less studied than Lactobacillus ( Lan et al, 2023 ). Clostridium sensu stricto , the genus with the second-highest taxon weight in the cluster analysis, is one of the main genus detected in the feces of pigs after weaning ( Chen et al, 2017 ) and its relative abundance increases with age ( Gaire et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, other species such as Clostridium chartatabidum and Clostridium paraputrificum , detected in the intestines of cattle [ 80 ] and swine [ 81 , 82 ], were also found to be more abundant in these sites 3 and 4. We also observed that Turicibacter sanguinis , found in the swine gastrointestinal tract [ 83 ] and in environments influenced by swine waste [ 84 , 85 , 86 ], showed a high prevalence at sites 3 and 4.…”
Section: Discussionmentioning
confidence: 99%